Intersection of the Metaverse, Muslim Identity, and Radicalization Risks: A Global Systematic Review of Digital Religious Communication - Widyaningsih, Rindha; Megia, Francisco Villacampa (Fakultas Dakwah UIN Saizu Purwokerto, 2026)
This study aims to explore the intersection of the metaverse, Muslim identity, and the risks of radicalization in the context of digital religious communication. The central research questions are: (1) What metaverse platforms do Muslim communities employ for religious practices and communication? (2) How is the representation of muslim identity in virtual spaces? (3) What radicalization risks and recruitment strategies emerge? Methodologically, a Systematic Literature Review (SLR) was conducted following PRISMA guidelines. Data were collected from reputable journal databases, leaving 68 studies for synthesis. The findings demonstrate that Muslim communities utilize various digital platforms for daʿwah, ritual practices, and the expression of identity. The platforms include mainstream social media as well as immersive environments based on Virtual Reality (VR) and Augmented Reality (AR). The utilization of these platforms also presents a potential risk of radicalization through algorithmic amplification. Such risks manifest as avatar manipulation and identity forgery. Gaming ecosystems are equally exploited to facilitate extremist grooming. The metaverse provides opportunities to enhance religious communication; however, it also introduces vulnerabilities that require careful attention and mitigation.